Value- based leadership: becoming best partner and accountable team partner - Mat Zin, Nora (2021)
Behaviour of successful leaders includes empowering and enabling team to inspired a shared vision. As a partner in a team, they ignite the spark and create the mutual and respectful working environment. This is also driven by specific values in the leader such as integrity, empathy and humility. The outcome can be seen in the development of trusting partnership and sense of empowerment. The values drive a person to be an accountable team partner. The way forward is to engage in the best partnership based on the value driven behavioural change to achieve the balance and harmonious human being.